Toward energy-efficient buildings in Oman - A. H. Al-Badi; S. N. Al-Saadi (International Journal of Sustainable Energy, 2020)
Energy consumption has drastically increased in buildings in several places over the last decade owing to economic growth and population increase. Substantial energy saving can be attained if these buildings are designed in a proper way. This paper presents a case study about energy-efficient building methods that can be applied in Oman. A residential building was taken as a case study which was evaluated using DesginBuilder software. Several energy efficiency measures (EEMs) such as thermal insulation in walls and roof, high-performance glazing, external shading, LED lights and energy-efficient air conditioning were evaluated. Total energy consumption was reduced by as much as 37%. Adding 6 kW PV and solar water heater can reduce the annual consumption by more than half when compared to the business as usual case. In addition to the technical feasibility, the design with EEM and renewable energy systems was found to be economically attractive. The results from this study provide energy-efficient design guidelines for residential sector in hot climates.